2011
DOI: 10.1007/s11738-011-0753-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in biomass allocation and phenolic compounds accumulation due to the effect of light and nitrate supply in Cecropia peltata plants

Abstract: Cecropia peltata is popularly known as ''guarumbo'' in Mexico and is used in traditional medicine for treatment of diabetes mellitus. C. peltata plants were cultivated in a hydroponic system under controlled conditions. Gradients of light (20, 30 and 100 lmol m -2 s -1 ) and nitrate concentrations (13, 2 and 0.2 mM) were applied to estimate their effect on biomass allocation and accumulation of bioactive (chlorogenic acid and isoorientin) phenolic compounds over a 28-day period. According to carbon nutrient ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
1
7
0
4
Order By: Relevance
“…Phenolic compounds, including tannins, are a significant component of plant secondary metabolites (Izquierdo et al 2011). Estimated to be the fourth most abundant biochemical produced by vascular plant tissue after cellulose, hemicellulose, and lignin, tannins represent a significant portion of terrestrial biomass C (Hernes and Hedges 2000;Hernes et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds, including tannins, are a significant component of plant secondary metabolites (Izquierdo et al 2011). Estimated to be the fourth most abundant biochemical produced by vascular plant tissue after cellulose, hemicellulose, and lignin, tannins represent a significant portion of terrestrial biomass C (Hernes and Hedges 2000;Hernes et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Photo-inhibition induced by low temperature or water stress is the proposed mechanism for the increase in toxic oxygen compounds under these conditions (El-Saht 1998, Zobayed et al 2007). Other abiotic conditions, such as exposure to high levels of sunlight, may also increase levels of oxidative stress in plants (Anjum et al 2011, Izquierdo et al 2011). Intra- and interyear variation in environmental conditions may explain differences in antioxidant capacity between seasons and years.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, stress from ultraviolet (UV) light, temperature extremes, pathogen infection, and browsing by herbivores is often correlated with higher concentrations of polyphenols with antioxidant capacity (Bahnweg et al 2000, Kondo and Kawashima 2000, Yarnes et al 2008, Mizumachi et al 2012). For example, chlorogenic acid has antioxidant properties and accumulates in plant tissue in response to high light (Izquierdo et al 2011) and elevated UV-B (Kondo and Kawashima 2000). Catechin, another polyphenol with antioxidant properties, increases in plants in response to inoculation with pathogenic fungi (Bahnweg et al 2000).…”
mentioning
confidence: 99%
“…Presence of phenols was observed, as well as alkaloid type compounds, saponins, sesquiterpene lactones, lactones, and coumarins. Studies in other species have demonstrated these compounds, mainly chlorogenic acid in Cecropia glaziovii, Cecropia obtusifolia, Cecropia pachystachya, and Cecropia peltata (Andrade-Cetto and Wiedenfeld, 2001;Lacaille et al, 2001;Herrera-Arellano et al, 2004;Andrade-Cetto et al, 2007;Rocha et al, 2007a;Nicasio-Torres et al, 2009;Andrade-Cetto and Vázquez, 2010;Aragão et al, 2010;Arend et al, 2011;Mora Izquierdo et al, 2011;Nicasio-Torres et al, 2011;Petronilho et al, 2012;Beringhs et al, 2013;Cruz et al, 2013). In addition, for Cecropia glaziovii caffeic acid (Arend et al, 2011;Beringhs et al, 2013); protocathechuic acid in Cecropia glaziovii (Lacaille et al, 2001); alkaloids in Cecropia pachystachya, Cecropia glaziovii, and Cecropia peltata (King and Haddock, 1959;Consolini and Migliori, 2005;Ninahuaman et al, 2007).…”
Section: Preliminary Phytochemical Analysismentioning
confidence: 98%